PERANCANGAN KEBIJAKAN ELEKTRIFIKASI SISTEM SEPEDA MOTOR INDONESIA DENGAN PENDEKATAN DINAMIKA SISTEM - Fawwaz Abiyyu Anvilen, Muhammad
Motorcycle is the main mode of choice for mobility in Indonesia. Every year in Indonesia, motorcycles emit 50 Mt CO2-eq to the atmosphere, out of 157 Mt CO2-eq emitted by the transportation system as a whole. This causes three problems, i.e., (1) climate change, (2) air pollution, and (3) trade-off dilemma between economic growth and carbon emission. To cope with these problems, the electrification of the transportation system is widely proposed, in particular the electrification of motorcycle due to (1) its dominant presence, (2) its low cost of ownership, (3) its attractiveness in tight urban areas, and (4) its simpler manufacturing process. The Indonesian government has planned multiple electrification scenarios based on a black box approach without an explicit causal model which makes comparison hard to do. System dynamics approach is used in this research to model the electrification of the Indonesian motorcycle system. The model is comprised of five agents (User, Manufacturer, Infrastructure Provider, Conversion Service Provider, and Government) and the important feedback loops among them. The simulation runs from 2023 to 2045. Based on the decision variables and constraints that the Government faces, 2904 policy scenarios were formulated. Three top policy scenarios were selected based on the performance measures of electric motorcycle stock and yearly total emission at the end of simulation. Each of these three policy scenarios increases the stock of electric motorcycles by 6 million units, from 52 million units at baseline in 2045. None of the policy scenarios was found to have a yearly total emission in 2045 that is lower than that in 2023. These three policy scenarios suggest that the Government needs to focus on imposing incentives on electric motorcycles, conversions, and swapping stations; rather than imposing disincentives on conventional motorcycles and gas filling stations. Furthermore, the Government has to implement a grid decarbonization scenario that is more ambitious than the most ambitious one it has right now. In implementing these policies, the Government also has to pay attention on whether the system is in a suppy-constrained or demand-constrained regime to attain policy effectiveness.